An Overview of the Cross-Border Mergers and Acquisitions - Tsuji, Chikashi (Archives of Business Research, 2015)
This paper examines the cross-border Mergers and acquisitions (M&As) in 13 international countries, and our analyses reveal the following evidence. 1) First, over the four years from 2010 to 2013, the larger amounts of acquired firms are observed in the US, UK, and Australia. 2) Second, we also find that, over the four years from 2010 to 2013, the larger amounts of acquiring firms are seen in the US, UK, France, Japan, and China. 3) Third, in the recent years, the higher growth rates of the amounts of acquiring firms are observed in China, Singapore, and Japan. On the other hand, the negative growth rates of the amounts of acquiring firms are seen in Switzerland and Russia. 4) Fourth, in France, Japan, and China, the differences between the amounts of acquiring firms and those of acquired firms are positive. Contrary to this, the differences between the amounts of acquiring firms and those of acquired firms are negative in Australia and Russia. Hence it is understood that in France, Japan, and China, more firms buy other countries’ firms in cross-border M&As whilst Australian and Russian firms are generally bought by other countries’ firms. Keywords: Cross-border M&A; International mergers